Interference of endogenous benzoic acid with the signatures of sulfonic acid derivatives and carbohydrates in fermented dairy products - Wei Jia; Xin Wang; Lin Shi (Fundamental Research)
Endogenous benzoic acid causes detrimental effects on public health, but the underlying mechanisms often remain elusive. Benzoic acid (0.00–40.00 mg L−1) was detected from sixty fermented goat milk samples in six replicates, indicating the existence of endogenous benzoic acid. Herein, we investigated the effects of benzoic acid on the variations of metabolome and proteome signatures in fermented goat milk via integrative metabolomics (LOQ 2.39–98.98 μg L−1) and proteomics approach based on UHPLC-Q-Orbitrap HRMS. Explicitly, benzoic acid reduced the content of taurine (7.06–4.80 mg L−1) and hypotaurine (3.86–1.74 mg L−1) due to a significant decrease in the levels of glutamate decarboxylase 1 by benzoic acid. The reduction in lactose (7.13–5.31 mg L−1) and d-galactose (4.39–3.37 mg L−1) content was related to the decrease in α-lactalbumin and β-galactosidase levels, respectively, in fermented goat milk containing 40.00 mg L−1 benzoic acid. Meanwhile, the levels of maltose (22.84–16.53 mg L−1) and raffinose (4.19–3.10 mg L−1) progressively decreased with increasing benzoic acid concentrations (0.00–40.00 mg L−1), which had detrimental effects on the nutritional quality of fermented goat milk. Additionally, the concentration of benzoic acid and fermentation temperature are the most important factors to control the loss of nutrients in fermented dairy products.